2011
DOI: 10.1111/j.1600-0501.2010.02119.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of margin location on the amount of undetected cement excess after delivery of cement‐retained implant restorations

Abstract: The amount of residual cement after cleaning increased as the restoration margins were located more subgingivally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
2
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 21 publications
7
167
2
8
Order By: Relevance
“…However, this option treatment needs assessment of the potential clinical benefit and risk associated with the technique. The liability of excess cement remainder in the periodontal area and its consequences has been discussed as an adverse outcome, in case with abutment margin depths and immediate cemented restoration (12), which may be prevented with abutment that allow screw-retained crowns (6). Another disadvantage associated with definitive abutment after surgery is the difficulty of selecting the appropriate definitive standard abutment immediately after implant insertion, concerned to high soft tissue and wall bone variance (12) that can be prevented by using customized abutments (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, this option treatment needs assessment of the potential clinical benefit and risk associated with the technique. The liability of excess cement remainder in the periodontal area and its consequences has been discussed as an adverse outcome, in case with abutment margin depths and immediate cemented restoration (12), which may be prevented with abutment that allow screw-retained crowns (6). Another disadvantage associated with definitive abutment after surgery is the difficulty of selecting the appropriate definitive standard abutment immediately after implant insertion, concerned to high soft tissue and wall bone variance (12) that can be prevented by using customized abutments (13).…”
Section: Introductionmentioning
confidence: 99%
“…So, it is concluded that full removal of excess resin cement is must even if with customized implant abutment. (27). So, it is very difficult to remove an excess of resin cement from the implant abutment (28).…”
Section: Discussion:-mentioning
confidence: 99%
“…In general, the results of both abutment materials showed only minor statistically significant differences. Evidence-based review assessed the outcome of abutment materials on alveolar bone loss, was drawn in the same decision as previous, (27). Based on visceral, human biology and different clinical studies, abutments materials (zirconia & titanium) showed no difference in effect on alveolar bone stability.…”
Section: Discussion:-mentioning
confidence: 99%
“…However, inadequate removal of excessive cement at the time of implant cementation may lead to a complication, cement-induced peri-implantitis 69 . The probability of cement to remain in the peri-implant sulcus is high when margins of the restoration are placed 1.5mm to 3mm subgingivally 70 . In a recent systematic review, Pesce et al 71 appraised the currently available scientific evidence to assess the role played by cement excess and misfitting components on the development of peri-implantitis.…”
Section: Bruxismmentioning
confidence: 99%